2011
DOI: 10.1002/sia.3407
|View full text |Cite
|
Sign up to set email alerts
|

ToF‐SIMS characterization of the lipid layer on the hair surface. I: the damage caused by chemical treatments and UV radiation

Abstract: In this study, we investigated how the lipids bound to the outermost surface of human hair are affected by chemical treatments such as hair bleach and ultraviolet (UV) radiation using time-of-flight secondary ion mass spectrometry (ToF-SIMS). Many lipid components are bound covalently via a thioester or ester linkage on the outermost surface of hair. We studied how these components are changed by chemical treatment. It was found that the fatty acids covalently bound via a thioester linkage are removed more eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Consequently, it was confirmed that the surface cuticles of the subjects elder than 40 are prone to be broken and this phenomenon is promoted by aging . It has been variously reported that reduction of 18‐MEA badly affects hair and that chemical treatments, such as bleaching, cause its drastic loss . In this study, it was revealed that aging also causes loss of 18‐MEA, especially in the age range elder than 40.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Consequently, it was confirmed that the surface cuticles of the subjects elder than 40 are prone to be broken and this phenomenon is promoted by aging . It has been variously reported that reduction of 18‐MEA badly affects hair and that chemical treatments, such as bleaching, cause its drastic loss . In this study, it was revealed that aging also causes loss of 18‐MEA, especially in the age range elder than 40.…”
Section: Discussionmentioning
confidence: 67%
“…It has been variously reported that reduction of 18-MEA badly affects hair and that chemical treatments, such as bleaching, cause its drastic loss. 6,[11][12][13][14][15] In this study, it was revealed that aging also causes loss of 18-MEA, especially in the age range elder than 40. A number of significant changes in hair properties (diameter, density, luster, bending elasticity, lipids, minerals, etc.…”
Section: Discussionmentioning
confidence: 79%
“…The 18‐MEA existing on the hair surface is detected as the negative molecular ion peak at m / z 341, the molecular ion peak of 18‐MEA . The oxidative cleavage of thioester bonds was evaluated by monitoring the change in the peak m / z 341 intensity . Figure shows the dependence of the decrease of the peaks at m / z 341 and m / z 76.…”
Section: Resultsmentioning
confidence: 99%
“…The surface damage of hair leads to changes in the physical properties such as increase in hydrophilicity and friction, which decreases hair quality. In previous studies it was revealed that serious damage leading to cleavage of disulfide bonds in cystine and decreasing of the fatty acids occur on the hair surface as shown in Fig. .…”
Section: Introductionmentioning
confidence: 99%
“…Even if the hair originally includes much melanin, the damages by UV exposure might be promoted by colouring and bleaching treatment, because of remaining agents and denaturation of hair itself [3]. It is also reported that more than 90% of the 18-MEA was removed by UV radiation with corresponding exposure for three summer months [4]. By elucidating the mechanism of oxidative damage by chemicals and UV, a guideline to prevent the hair damage would be clarified.…”
Section: Introductionmentioning
confidence: 99%